PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, GAYA KEPEMIMPINAN TRANSAKSIONAL DAN BUDAYA ORGANISASI TERHADAP PERILAKU INOVATIF (Stusi Pada Kantor Badan Penanggulangan Bencana Daerah DIY) - Afip Nurhidayat; Epsilandri Septyarini (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2021)
This study aims to determine the partial effect of transformational leadership style on innovative behavior, transactional leadership style on innovative behavior, the influence of organizational culture on innovative behavior and simultaneously the influence of transformational leadership style, transactional leadership style and organizational culture on innovative behavior. This study used a census sample with 43 respondents and the data collection technique was a questionnaire. This study used data quality test, classical assumption test, multiple linear regression analysis, coefficient of determination. The results showed that the transformational leadership style had a positive and significant effect on innovative behavior. The transactional leadership style has a positive and insignificant effect on innovative behavior. The organizational culture has a positive and significant effect on innovative behavior. Simultaneously transformational leadership style, transactional leadership style and organizational culture have a significant effect on innovative behavior. Keywords: Leadership Style, Organizational Culture and Innovative Behavior